VALIDITAS BAHAN AJAR JENIS IKAN DI SUNGAI PANJARATAN PADA KONSEP VERTEBRATA SMA KELAS X - Meyninda Destiara; Mochamad Arief Soendjoto; Dharmono Dharmono (Universitas Lambung Mangkurat, 2018)
Abstract: Changes in the curriculum requires students to be more active, creative, and love of nature. Then, the addition of learning resources should also be emphasized, that is not the lack of information learned. Source of learning is learning system components are designed, selected, used to create a complete learning and controlled. Exploiting local potential to become a reference source of student learning, the material vertebrates. Vertebrates material is one material that is easily found in the neighborhood. One type of Vertebrates are easy to find fish. Panjaratan river is one of the rivers that have quite a lot of fish that can potentially be used as an additional reference source of learning. This research aimed to describe the results of the development of teaching materials of the river fish species Panjaratan in valid criteria. Research method used Research and Development. It contains how to develop teaching materials with some phase like validity by expert, and its revise. The data source used was involved 3 lecturer Lambung Mangkurat University and students from Pelaihari Senior High School 1. The results showed teaching materials are made is quite valid based on the validation expert (81,2%) and partner teachers (87,9%), and the test showed that the readability of teaching materials by students is worth using.Keywords: valid, teaching materials, river, pisces